Grammar as processor : a distributed morphology account of spontaneous speech errors - Pfau, Roland (Linguistik aktuell, 2009)
Spontaneous speech errors provide valuable evidence not only for the processes that mediate between a communicative intention and the articulation of an utterance but also for the types of grammatical entities that are manipulated during production. This study proposes an analysis of speech errors that is informed by grammar theory. In particular, it is shown how characteristic properties of erroneous German utterances can be accounted for within Distributed Morphology (DM). The investigation focuses on two groups of errors: Errors that result from the manipulation of semantic and morphosyntac.